Towards codification of thunderstorm/downburst using gust front factor: Model-based and data-driven perspectives. (15th November 2019) - Kwon, Dae Kun; Kareem, Ahsan
Highlights: Gust front factor framework revisited from model-based and data-driven perspectives. Closed-form expression concerning nonstationary fluctuations derived. Preliminary uncertainty analysis performed to assess the influence of uncertainties. Comparison of model-based GFF with a recently introduced data-based TRST made. Possible living codification concept invoking Design Thinking approach discussed. Abstract: Winds associated with gust fronts originating from a thunderstorm/downburst exhibit rapid changes during a short time period which may be accompanied by changes in direction. For several decades, a number of studies have been focused on identifying the characteristics of such nonstationary gust front winds in a variety of manners such as experimental/numerical methods and full-scale measurements. Yet, beginning the dialogue on any guidelines for design practice has thus far not evolved, in part due to a limited consensus on such characteristics among studies in conjunction with paucity of available data needed for vetting and corroborating, which is further impacted by the presence of nonstationarity. In an effort to establishing a new design procedure for this type of wind load effect on structures, the gust front factor (GFF) framework has been proposed by authors that encapsulates both the kinematic and dynamic features of gust front induced wind effects on structures, which distinguish themselves from those experienced in conventional boundary layer flows. This study revisits the gust front factor framework seeking to take the next step toward a possible initial framework for codification of gust front winds from model-based and data-driven perspectives. A modular and extensible web-enabled framework to estimate gust front related wind load effects is envisaged to rationally and holistically quantify design loads. This would promote design practice to enhance disaster resilience of the built environment. In this context, a closed-form expression concerning nonstationary fluctuations for a case of a long pulse duration is derived to facilitate rapid evaluation of nonstationary turbulence effects. A preliminary uncertainty analysis is also carried out to assess the influence of uncertainties associated with the load effects of gust front winds and the reliability of GFF. In addition, a comparison of the model-based gust front factor with a recently introduced thunderstorm response spectrum technique to assess their relative performance is carried out. In view of the lessons learned from the history of the gust loading factor on codes and standards, a possible living codification concept through a learning and updating invoking the emerging "Design Thinking" approach is discussed.